2012
DOI: 10.1177/2048872612453923
|View full text |Cite
|
Sign up to set email alerts
|

Mortality and ST resolution in patients admitted with STEMI: the MOMI survey of emergency service experience in a complex urban area

Abstract: Background: Since 2001, the urban area of Milan has been operating a network among 23 cardiac care units, the 118 dispatch centre (national free number for medical emergencies), and the county government health agency called Group for Prehospital Cardiac Emergency. Methods and results:In order to monitor the network activity, time to treatment, and clinical outcome, a periodic survey, called MOMI 2 , was repeated two or three times a year. Each survey lasted 30 days and was repeated in comparable periods. Data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
(23 reference statements)
0
2
0
Order By: Relevance
“…The results obtained confirmed the high effectiveness in diagnosing ST-ACS by members of emergency medical response teams. Grieko et al [8], in research on the emergency medical response system in Italy, demonstrated the influence of ECG teletransmission on shortening the time between the first chest pains and the start of treatment. Tekerlsen et al [9], in their study on the Danish emergency medical system, where ambulance teams use ECG teletransmission, demonstrated a shortening of delays in the start of ST-ACS myocardial infarction treatment due to fast diagnosis and transport of patients directly to cardiology surgery wards.…”
Section: Discussionmentioning
confidence: 99%
“…The results obtained confirmed the high effectiveness in diagnosing ST-ACS by members of emergency medical response teams. Grieko et al [8], in research on the emergency medical response system in Italy, demonstrated the influence of ECG teletransmission on shortening the time between the first chest pains and the start of treatment. Tekerlsen et al [9], in their study on the Danish emergency medical system, where ambulance teams use ECG teletransmission, demonstrated a shortening of delays in the start of ST-ACS myocardial infarction treatment due to fast diagnosis and transport of patients directly to cardiology surgery wards.…”
Section: Discussionmentioning
confidence: 99%
“…4,5 Starting from 2006, in the Milan urban area a working group collecting 23 Cardiology Units and the 118 Dispatch Center (the Italian free-toll number for emergencies), performed monthly data collections twice a year on all patients admitted to any hospital in Milano with coronary artery disease (MOMI 2 : MOnth MOnitoring Myocardial Infarction in MIlan survey). The statistical analysis of the collected data [6][7][8] confirmed the time of first ECG teletransmission as the most important factor to guarantee a quick access to an effective treatment for patients. Since 2008, a project named PROMETEO (PROgetto sull'area Milanese Elettrocardiogrammi Teletrasferiti dall'Extra Ospedaliero) has been started with the aim of spreading the intensive use of ECG as pre-hospital diagnostic tool.…”
Section: Introductionmentioning
confidence: 99%